Optimization of CNC milling parameters using the response surface method for aluminum 6061 - Indaka, Arifin; Wahyudi, Bagus (Jurnal Polimesin, 2024)
The manufacturing sector is constantly seeking ways to optimize the machining process, specifically for 3-axis CNC machines. This study aims to identify the optimal parameter values that result in the lowest roughness and the highest process capability in 3-axis CNC milling. The roughness level (Ra) of the product is primarily influenced by factors such as feed rate, spindle speed, and depth of cut. Additionally, the reliability of the machining process was analyzed to evaluate its ability to consistently achieve low roughness values and to validate the process capability of the VH850L3 series 3-axis CNC milling machine. The suggested approach for this analysis was the RSM central composite design method, which involved conducting experiments under various input conditions. The results indicated that the feed rate had the most significant impact on roughness, followed by the spindle speed, while the depth of cut had no effect. The parameters that resulted in the lowest roughness response were a spindle speed of 2589.76 rpm, a depth of cut of 0.159 mm, and a feed rate of 247.731 mm/min. These parameter values were tested on a 3-axis CNC machine, and the resulting data exhibited variations. Data processing revealed that the machine still performed optimally in the machining process, as indicated by the value of . However, the milling process deviates from the standard target, as the response value shows significant variation with a Cpk value 1.